Revisiting trade and growth nexus in South Africa: Fresh evidence from a new measure and Augmented VAR framework: Trade-growth nexus in South Africa - Udeagha, Maxwell Chukwudi; Ngepah, Nicholas (Journal of Income Distribution®, 2024)
Ignoring structural breaks, which are predominantly pervasive in macroeconomic data may lead to misspecified models and spurious inferences. Empirical evidence connecting trade to economic growth has been mixed and inconclusive. This paper revisits the trade-growth nexus for South Africa by using an innovative proxy of trade openness proposed by Squalli and Wilson (2011) and employing the second-generation econometric procedures, which take into consideration the multiple structural breaks that have been largely ignored by the previous studies. Contrary to the previous literature, the new proxy of trade openness is constructed to take into consideration both South Africa’s trade share of its GDP and its relative size of trade in relation to the world trade in a specified period of time. Adopting this novel approach to capture openness, the study uses the augmented vector autoregressive (VAR) methodology developed in Toda and Yamamoto (1995) and leverages on newly developed econometric techniques by modelling and including relevant variables initially omitted in earlier studies, which help to elucidate the contradictory results from previous studies on the South Africa’s economy. The empirical findings provided the following insights: (i) a long-run steady state exists among the variables under review; (ii) regarding the trade-growth nexus, the results of the short-run effects are materially different from those of the long-run effects: while trade openness significantly improves economic growth in the short run, it has a measurably detrimental consequence on it in the long run; (iii) a bi-directional relationship is found between economic growth (InGDPPC) and trade openness (InOPEN); (iv) similarly, bi-directional causal relationships are seen between economic growth (InGDPPC) and Information, communication and technology (InICT); economic growth (InGDPPC) and foreign direct investment (InFDI); (v) unidirectional relationships are found running from capital-labour ratio(InKL), expenditure on human capital development (InHC) and expenditure on health (InHEA) to economic growth (InGDPPC). Vital policy implications could be learned from the empirical results.